Expression Profiling and Function Analysis Identified New Cumulus Cells-Expressed Genes and miRNAs Predictive of Oocyte Developmental Potential - Min Zhang; Meng-Meng Wang; Fa-Li Zhang; Nan He; Ming-Jiu Luo; Shuai Gong; Fu-Yin Fu; Hong-Jie Yuan; Jie Zhang; Jing-He Tan (Cells)
Although prior studies have identified cumulus cells (CCs)-expressed genes and miRNAs that regulate cumulus expansion and/or CC apoptosis and may serve as markers for selecting competent oocytes and embryos, there remains an urgent need to identify CCs-expressed genes and miRNAs whose expression levels are directly correlated with oocyte developmental potential (DP). In this study, we first established CC models from mouse cumulus-oocyte complexes (COCs) that exhibited significantly different DP following in vitro or in vivo maturation. Subsequently, we performed mRNA/miRNA sequencing and functional analyses using these in vitro and in vivo CC models. We identified and validated Spp1, Fn1, Sdc1, and Ngf as DP-beneficial genes; Fos and Jun as DP-detrimental genes; and miR-7686-5p, miR-133a-3p, novel-miR-239, novel-miR-193, and miR-339-5p as DP-detrimental miRNAs. Finally, by employing a well-in-well activation/embryo culture system that enables tracking the COC origin of CCs and embryos, we further validated Spp1 and Ngf as DP-beneficial genes, Jun as the DP-detrimental gene, and miR-7686-5p, novel-miR-239, and miR-339-5p as DP-detrimental miRNAs. In conclusion, we identified and validated new sets of CCs-expressed genes and miRNAs whose expression levels were directly correlated with oocyte DP. These newly identified genes and miRNAs may serve as potential biomarkers for selecting competent oocytes and embryos.